Desenvolvimento de célula hidrotérmica para obtenção de compostos nanocristalinos de alta pureza - Barrado, Cristiano Morita (Universidade Federal de São Carlos, 2008)
Due to the growing advances obtained in nanomaterials science, almost all technological sectors have invested in nanotechnology. It is expected technological improvements in a wide range of products, from the most conventional to nanostructured, as nanocomposites and nanoelectronics materials. Several techniques have been proposed in the literature aiming the search of these materials in a high purity grade. However, some problems to this goal persist, as the use of reactants with impurities of hard elimination and difficulties in the crystallization process, implying in a poor particle growth control. The hydrothermal synthesis has a great advantage for using few steps during the synthesis process and lower temperatures of prodution. Despite the advantages in the process, the cost of commercial equipments not adequated to this synthesis is around US$ 10,000.00 to 20,000.00, expensive values to Brazilian conditions. Also, there is not a brazilian equipment with adequate control and manipulability so far. These facts impair the dissemination of the processing technique. In this way, the main goal of this project is the construction of a hydrothermal system using brazilian materials and its application to the OPM-Hydrothermal hybrid synthesis to obtain technological materials. The association of the techniques enabled the union of the main features of each method leading to a high purity and high crystalline product, in soft solution condition in which the amorphous precipitate obtained by the chemically clean route OPM was crystallized in a soft process (hydrothermal), avoiding calcination. Crystalline phases of TiO2 were obtained at 200oC / 2 hours as rutile nanorods (pH = 0) and anatase from nanoparticles (pH = 2 to 8) to nanorods (pH = 10) and nanoneedles (pH = 12). Pure crystalline PbTiO3 and Pb(Zr50Ti50)O3 were obtained with cubic structure at 150 and 200oC / 2 hours, depending on the Pb stoichiometry adopted.
Development of a hydrothermal cell to obtain high purity nanocrystalline compounds
Keywords: Físico-química; Síntese hidrotérmica; Óxido de titânio; Titanato de chumbo; Titanato zirconato de chumbo (PZT); CIENCIAS EXATAS E DA TERRA::QUIMICA